VEGF-A promotes cardiac stem cell engraftment and myocardial repair in the infarcted heart. (15th March 2015) - Tang, Jun-Ming; Luo, Bin; Xiao, Jun-hui; Lv, Yan-xia; Li, Xiao-lin; Zhao, Jin-he; Zheng, Fei; Zhang, Lei; Chen, Long; Yang, Jian-Ye; Guo, Lin-Yun; Wang, Lu; et al.
Abstract: Background: The objective of this study was to determine whether vascular endothelial growth factor (VEGF)-A subtypes improve cardiac stem cell (CSC) engraftment and promote CSC-mediated myocardial repair in the infarcted heart. Methods: CSCs were treated with VEGF receptor (VEGFR) inhibitors, VCAM-1 antibody (VCAM-1-Ab), or PKC-α inhibitor followed by the treatment with VEGF-A. CSC adhesion assays were performed in vitro. In vivo, the PKH26-labeled and VCAM-1-Ab or PKC-α inhibitor pre-treated CSCs were treated with VEGF-A followed by implantation into infarcted rat hearts. The hearts were then collected for measuring CSC engraftment and evaluating cardiac fibrosis and function 3 or 28 days after the CSC transplantation. Results: All three VEGF-A subtypes promoted CSC adhesion to extracellular matrix and endothelial cells. VEGF-A-mediated CSC adhesion required VEGFR and PKCα signaling. Importantly, VEGF-A induced VCAM-1, but not ICAM-1 expression in CSCs through PKCα signaling. In vivo, VEGF-A promoted the engraftment of CSCs in infarcted hearts, which was attenuated by PKCα inhibitor or VCAM-1-Ab. Moreover, VEGF-A-mediated CSC engraftment resulted in a reduction in infarct size and fibrosis. Functional studies showed that the transplantation of the VEGF-A-treated CSCs stimulated extensive angiomyogenesis in infarcted hearts as indicated by the expression of cardiac troponin T and von Willebrand factor, leading to an improved performance of left ventricle. Blockade of PKCα signaling or VCAM-1 significantly diminished the beneficial effects of CSCs treated with VEGF-A. Conclusion: VEGF-A promotes myocardial repair through, at least in part, enhancing the engraftment of CSCs mediated by PKCα/VCAM-1 pathway. Graphical abstract: Highlights: VEGF-A treatment enhanced CSC adhesion to ECs through induction of VCAM-1, not ICAM-1, which required PKCα signaling in vitro. CSC activated in vitro with VEGF-A amplified CSC engraftment in the sites of infarcted heart through PKCα /VCAM-1 signaling in vivo. CSC activated in vitro with VEGF-A increased angiomyogenesis in myocardium, and improved cardiac function of infarcted heart.